Modulatory Effect of Lippia alba Essential Oil on the Activity of Clinically Used Antimicrobial Agents on Salmonella typhi and Shigella dysenteriae Biofilm - Andressa Batista; Hilania Dodou; Matheus Rodrigues; Pedro Pereira; Gleilton Sales; Suelen Medeiros; Nádia Nogueira (MDPI AG, 2018)
The essential oil obtained from the leaves of Lippia alba (Mill.) N.E. Brown (Verbenaceae) has shown great pharmacological potential as an analgesic, antispasmodic, and antimicrobial agent. The aim of this study was to evaluate the modulatory effect of Lippia alba essential oil (LaEO I) on the activity of clinically used antimicrobial agents on Salmonella enterica serovar Typhi (Salmonella typhi) and Shigella dysenteriae biofilms. The Minimum Inhibitory Concentration of LaEO I (MICLaEO I) was determined by the microdilution method, and the effect of LaEO I on the activity of clinically used antimicrobials was assessed by the Checkboard method. The values obtained from MICLaEO I and ciprofloxacin were used to evaluate the effect of time of exposure on cell viability. LaEO I main components were geranial (34.2%), neral (25.9%), and myrcene (12.5%). The MICLaEO I was 1 mg/mL for both strains. LaEO I positively modulated the action of ciprofloxacin, cefepime, and ceftriaxone. After the first hour of treatment with MICLaEO I, the cell viability of the strains showed a 5 log10 CFU/mL reduction, and the LaEO I-CIP association was able to inhibit growth during the first 6 h of the test. Regarding the anti-biofilm activity, MICLaEO I was able to reduce the biofilm mass of Salmonella typhi by 61.2% and of Shigella dysenteriae by 38.9%. MICLaEO I was not able to eradicate the preformed biofilm; however, there was a reduction in the biofilm microbial viability. LaEO I has the potential to be used as an antimicrobial agent and interferes with biofilm formation; also, it is able to reduce cell viability in preformed biofilm and synergistically modulate the activity of ciprofloxacin.